THE EFFECT OF BANK CHARACTERISTICS AND GOVERNANCE ON THE RATE OF RETURN IN ISLAMIC RURAL BANK - Rozaq Muhammad Yasin (IAIN Surakarta, 2021)
The difference in profit sharing on investment funds placed by customers and shareholders can create agency problems. This study aims to analyze the effect of bank characteristics and governance on the rate of return on investment received by depositors and shareholders as the main investors in the operations of the Islamic Rural Bank. This study used panel data from 10 Islamic Rural Bank in the Special Region of Yogyakarta from 2013 to2020. The results showed that all bank characteristic proxies, namely financing growth, financing structure, efficiency, and financing quality significantly affected the rate of return received by depositors and shareholders, except for the efficiency variable which did not significantly affect the rate of return on investment for depositors. Islamic Rural Bank governance structure needs to pay attention to the ownership ratio, capital adequacy ratio, and the effectiveness of supervision by the Sharia Supervisory Board to maintain a competitive return on investment so that it is attractive to both depositors and shareholders.